Worsening of Controlled Attenuation Parameter and Metabolic Profile After HCV Cure in People with HIV as a Sign of Steatosis - Alessia Siribelli; Sara Diotallevi; Laura Galli; Camilla Muccini; Giulia Morsica; Riccardo Lolatto; Tommaso Clemente; Emanuela Messina; Costanza Bertoni; Caterina Uberti-Foppa; Antonella Castagna; Hamid Hasson (Viruses)
In HCV-coinfected people with HIV (PWH), there are still conflicting data regarding the long-term metabolic impact of HCV eradication. The aim of the study is to investigate long-term changes in controlled attenuation parameter (CAP) and metabolic profile after sustained virological response (SVR) post-direct acting antivirals (DAAs) in PWH. This is a retrospective observational study including individuals with HIV/HCV coinfection, followed as outpatients at San Raffaele Hospital, who achieved SVR post-DAAs. Individuals were assessed for metabolic parameters before and after the start of DAAs. Univariate and multivariate mixed linear models were calculated to estimate crude mean changes in CAP, metabolic parameters, and weight; slopes were reported with the corresponding 95% confidence intervals (95% CI). Overall, during a median follow-up of 4.02 years (interquartile range, IQR 3.04–4.80), the mean percent increase in CAP was 2.86/year (p < 0. 0001), and the mean decrease in stiffness was –4.28 (p = 0.003). Additionally, total cholesterol (p < 0.0001), high-density lipoprotein (HDL) cholesterol (p = 0.001), triglycerides (p < 0.0001), glucose (p < 0.0001), and Body Mass Index (BMI) (p < 0.0001) increased over time. A long-term follow-up in PWH with SVR post-DAAs showed an overall significant increase in CAP and worsening of the metabolic profile, suggesting a higher risk of developing liver steatosis and metabolic alterations over time.